Addition of lactic acid levels improves the accuracy of quick sequential organ failure assessment in predicting mortality in surgical patients with complicated intra-abdominal infections: a retrospective study - Yun Tae Jung; Jiyeon Jeon; Jung Yun Park; Myung Jun Kim; Seung Hwan Lee; Jae Gil Lee (World Journal of Emergency Surgery, 2018)
Abstract Background The quick sequential organ failure assessment (qSOFA) alone has a poor sensitivity for predicting mortality in patients with complicated intra-abdominal infections, and plasma lactate levels have been shown to have a strong association with mortality in critically ill patients. Therefore, this study aimed to compare the performance of qSOFA with a score derived from a combination of qSOFA and serum lactate levels for predicting mortality in surgical patients with complicated intra-abdominal infections. Methods This retrospective study was performed at a university hospital. The medical records of 457 patients who presented to the emergency department (ED) between January 2008 and December 2016 and required emergency gastrointestinal surgery for a complicated intra-abdominal infection were reviewed retrospectively. qSOFA criteria, sequential organ failure assessment (SOFA) scores, and plasma lactate levels during their ED stay were collected. We performed area under receiver operating characteristic (AUROC) curve and sensitivity analysis to compare the performance of qSOFA alone with that of a score derived from the use of a combination of the qSOFA and lactate levels for predicting patient mortality. Results Fifty patients (10.9%) died during hospitalization. The combined qSOFA and lactate level score was superior to qSOFA alone (AUROC = 0.754 vs. 0.717, p = 0.039, respectively) and comparable to the full SOFA score (AUROC = 0.754 vs. 0.795, p = 0.127, respectively) in predicting mortality. Sensitivity and specificity of qSOFA alone were 46 and 86%, respectively, and those of the combined score were 72 and 73%, respectively (p < 0.001). Conclusion A score derived from the qSOFA and serum lactate levels had better predictive performance with higher sensitivity than the qSOFA alone in predicting mortality in patients with complicated intra-abdominal infections and had a comparable predictive performance to that of the full SOFA score.